Lluciapomaresius nisae, a new species of Ephippigerini (Orthoptera: Tettigoniidae: Bradyporinae) from the northeast of the Iberian Peninsula - Olmo-Vidal, Josep Maria (Zootaxa, 2017)
A new species of the genus Lluciapomaresius Barat, 2012 is described from Serra de Llaberia in Catalonia (in the northeast of Iberian Peninsula). Lluciapomaresius nisae n. sp. was collected in a Mediterranean pine forest dominated by European black pine (Pinus nigra) and secondarily by Calcicolous rosemary scrub. L. nisae is compared to L. panteli (Navàs, 1899) from which it can be separated mainly by the shape of the male cerci, the titillators and the male calling song. Also in the females by the protuberances at the base of the ventral valves of the ovipositor.